Non-Linear Static Analysis of Off-Road Vehicle Cabin ROPS Structure Using Finite Element Method - Kumar. T, Rajesh; R, Haridass; N V, Dhandapani; M, Dinakar (International Journal of Engineering and Technology, 2018)
The passive safety of operator is an important parameter to be evaluated when an automotive is considered. During life-threatening situations like vehicle rollovers, the safety of the operator can be ensured by the design of protective structure. The protective structure that safeguards the operator, is either an integral part of the cabin of the operator or an external structure outside the operatorâ€™s compartment. The major accidents occurring in military, construction and mining operations are disastrous due to absence of this structure. Thus an effective ROPS (Roll Over Protective structure) along with the corresponding FOPS (Fall Over Protective Structure) can be used for saving lives.Â Â